The lion the chock and the donkey (Malaysia : Mind to mind, 2018)
"The Lion, the Cock, and the Donkey" likely tells a story about these three different animals and how they interact. Perhaps they go on an adventure together, or maybe one of them needs help from the others. Given it's a story for kids, it will probably have a simple plot and a clear message about friendship, bravery, or cleverness.
Location: 3C
Keywords: Story book